Studi In Silico dari Metabolit Invertebrata Laut Indonesia terhadap Protein ACE2 dan Spike Protein SARS-CoV-2 Varian Omicron - Claus, Matheus Prayoga; Putra, Masteria Yunovilsa; Wibowo, Joko Tri; Yanuar, Arry (Jurnal Farmasi & Sains Indonesia, 2025)
Indonesia has a diverse marine biota with bioactive substances that may provide a way to overcome COVID-19. In this research, we explored secondary metabolites isolated from marine invertebrates in Indonesia. A total of 137 compounds from different types of invertebrates were screened against ACE2 and SARS-CoV-2 Omicron spike protein. In relation, molecular docking and ADMET prediction were investigated to find the best compound. A molecular dynamics study was performed to determine the stability of the binding between the compound and ACE2 and RBD of the Omicron spike protein virus receptor. The results showed that acanthomanzamine E and cortistatin L have prominent molecular docking properties as ACE2 and SARS-CoV-2 Omicron spike protein blockers with binding energies of -12.87 and -9.96 kcal, respectively. The ADMET results also showed that both compounds have a promising drug-likeness, with only minor exceptions in partition coefficient (logP) and half-life. In conclusion, acanthomanzamine E and cortistatin L have shown significant potential as lead compounds for drug targeting ACE2 and SARS-CoV-2 blockers.